Open longevity science ([Bentham Science Publishers], 2007)
Open Longevity Science was an Open Access online journal, which publishes research articles and letters in all areas of experimental and clinical research in geriatric medicine and aging science.
Keywords: Gerontology : Periodicals; Geriatrics : Periodicals; Aging : Periodicals; Aging; Longevity; Older people; Aging; Geriatrics; Longevity; Aged; Humans; Gérontologie : Périodiques; Gériatrie : Périodiques; Vieillissement : Périodiques; Vieillissement; Longévité; Personnes âgées; elderly; Geriatrics; Gerontology